2018
DOI: 10.2175/106143018x15289915807056
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in the Environment

Abstract: This review su mmarizes selected publications from 2017 highlighting the occurrence of antimicrobial resistance (AMR) genes in the environment with emphasis on the aquatic environment. The review also covers different treatment technologies being developed for AMR genes as an environmental contaminant. The progress made in the area of AMR gene databases and tools is also reviewed. Besides a brief introduction, the content is categorized into three main sections: i) Occurrence of AMR in the Environment, ii) Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Antibiotic resistance is one of the biggest public health challenges in every country over the world [1,2]. The economic costs, due to clinical interventions and productivity losses, account for 9 billion EUR and 20 billion USD in Europe and the USA, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic resistance is one of the biggest public health challenges in every country over the world [1,2]. The economic costs, due to clinical interventions and productivity losses, account for 9 billion EUR and 20 billion USD in Europe and the USA, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…(CPK) isolates in clinical settings are increasingly being reported [ 12 , 13 ]. Several studies including Waseem et al [ 14 ] have reported CPK and ARGs in non-clinical environments, Proia et al [ 15 ] (2018); Khan et al [ 16 ] in wastewater treatment plants (WWTPs), Uyaguari et al [ 17 ], in agricultural samples and Stange et al [ 18 ] in rivers and lakes. However, none of these studies investigated at the same time the occurrence of relevant carbapenem-resistance genes (CRGs) in isolates recovered from environmental samples.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of MDR organisms, resistance genes, and antibiotic residues in surface water bodies is well established outside Bangladesh, among similar settings in Asia (O'Flaherty and Cummins, 2017;Qiao et al, 2018;Waseem et al, 2018;Zhang et al, 2019;Singh et al, 2019;Reddy and Dubey, 2019;Ahammad et al, 2014). Natural flow of untreated wastewater into surface water bodies including rivers, lakes or canals is commonly observed in many LMICs and is likely a key driver of environmental transmission of clinically important antibiotic resistant organisms (Rabbani et al, 2017;Karkman et al, 2017;Islam et al, 2017).…”
Section: Discussionmentioning
confidence: 99%